Formulation and Characterisation of a Combination Captopril and Hydrochlorothiazide Microparticulate Dosage Form - Mellisa T. R. Chikukwa; Roderick B. Walker; Sandile M. M. Khamanga (MDPI AG, 2020)
Cardiovascular diseases such as hypertension and cardiac failure in South African children and adolescents are effectively managed long term, using a combination treatment of captopril and hydrochlorothiazide. The majority of commercially available pharmaceutical products are designed for adult patients and require extemporaneous manipulation, prior to administration to paediatric patients. There is a need to develop an age appropriate microparticulate dosing technology that is easy to swallow, dose and alter doses whilst overcoming the pharmacokinetic challenges of short half-life and biphasic pharmacokinetic disposition exhibited by hydrochlorothiazide and captopril. An emulsion solvent evaporation approach using different combinations of polymers was used to manufacture captopril and hydrochlorothiazide microparticles. Design of experiments was used to develop and analyse experimental data, and identifyoptimum formulation and process conditions for the preparation of the microparticles. Characterisation studies to establish encapsulation efficiency, in vitro release, shape, size and morphology of the microparticles were undertaken. The microparticles produced were in the micrometre size range, with an encapsulation efficiency >75% for both hydrochlorothiazide and captopril. The microparticulate technology is able to offer potential resolution to the half-life mediated dosing frequency of captopril as sustained release of the molecule was observed over a 12-h period. The release of hydrochlorothiazide of >80% suggests an improvement in solubility limited dissolution.